Roadbumps at the Crossroads of Integrating Behavioral and In Vitro Approaches for Neurotoxicity Assessment - Harry, G. Jean; McBride, Sandra; Witchey, Shannah K.; Mhaouty-Kodja, Sakina; Trembleau, Alain; Bridge, Matthew; Bencsik, Anna (Frontiers in Toxicology, 2022)
With the appreciation that behavior represents the integration and complexity of the nervous system, neurobehavioral phenotyping and assessment has seen a renaissance over the last couple of decades, resulting in a robust database on rodent performance within various testing paradigms, possible associations with human disorders, and therapeutic interventions. The interchange of data across behavior and other test modalities and multiple model systems has advanced our understanding of fundamental biology and mechanisms associated with normal functions and alterations in the nervous system. While there is a demonstrated value and power of neurobehavioral assessments for examining alterations due to genetic manipulations, maternal factors, early development environment, the applied use of behavior to assess environmental neurotoxicity continues to come under question as to whether behavior represents a sensitive endpoint for assessment. The question raised then is, why is rodent behavior a sensitive tool to the neuroscientist and yet, not considered such when used in pre-clinical or chemical neurotoxicity studies. Applying new paradigms and evidence on the biological basis of behavior to neurobehavioral testing requires a refinement of how such experiments are conducted to minimize variability and maximize information. This review presents relevant issues of methods used to conduct such test, sources of variability, experimental design, data analysis, interpretation, and reporting. It proposes that a refinement of the behavioral testing methods and an understanding of the subtle but pronounced differences will facilitate the integration of data obtained from in vitro and non-mammalian systems to understand the mechanisms and apical manifestation of neurotoxicity.